THE EFFECT OF GOOGLE FORM AS MEDIA TOWARDS STUDENTS’ READING COMPREHENSION - Eva Diana Tanjung; Putri Asilestari; Lusi Marleni (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to find out the effect of using Google Form as a media towards students' Reading comprehension. This was conducted to the eighth grade students at SMPN Satu Atap Danau Lancang in the learning year 2022/2023. The type of this research is quasi-experimental by comparing two groups, namely the control group and the experimental group. The sample used was class VIII A as the experimental group and class VIII B as the control group. The research instrument is a reading comprehension test which consists of 25 multiple choice questions. Based on the data analysis, the researchers obtained the results that the average value of the experimental class students was 81.14 and the average value of the control class was 72.76. The researcher used a T-test with the formula If Tcount Ttable, the hypothesis was accepted. If Tcount Ttable, the hypothesis is rejected. From the calculation results, it is found that tcount = 2.768 t-table = 1.683 in the degree of freedom (Na + Nb -2 = 21+ 21–2 = 40) and the level of significance is 0.008 0.05 (5%). That indicates that there is a significant effect of Google Form as a media towards students’ reading comprehension at SMPN 1 Atap Danau Lancang.